A nomogram for predicting mortality in patients with COVID-19-associated acute respiratory distress syndrome treated with veno-venous extracorporeal membrane oxygenation - K. A. Mikaelian; M. V. Petrova; E. V. Filimonova; S. A. Bazanovitch (Вестник анестезиологии и реаниматологии, 2024)
The objective was to develop a predictive model for assessing the risk of hospital mortality in patients with COVID-19-associated acute respiratory distress syndrome (ARDS) treated with veno-venous extracorporeal membrane oxygenation (VV-ECMO).Materials and methods. We carried out the analysis of case histories of 123 patients treated in the ICU № 7 of the Moscow City Clinical Hospital 52 during the COVID-19 pandemic period. All patients were treated with the VV-ECMO for COVID-19-associated ARDS according to current indications. We analyzed the characteristics potentially associated with mortality, after which we performed statistical analysis, on the basis of which we created the predictive model.Results. The overall-mortality rate was 87% (107/123). Independent predictors of death in patients with COVID-19 treated with the VV-ECMO were the maximum VV-ECMO blood flow rate, the period from the onset of the disease to mechanical ventilation, P/F prior to the VV-ECMO initiation and the fact of septic shock development during VV-ECMO. The quality of the prognostic model: AUC = 0.952 [0.909‒0.995], p < 0.001.Conclusions. The nomogram to assess the risk of death in patients with COVID-19 treated with the VV ECMO has been developed. It includes the assessment of the maximum VV-ECMO blood flow rate, the period from the onset of the disease to mechanical ventilation, P/F prior to the VV-ECMO initiation and the fact of septic shock development during VV-ECMO.